DETERMINANTS OF ANEMIA AMONG ADOLESCENT GIRLS: IMPLICATIONS FOR STUNTING PREVENTION - Amartha, Tecky Afifah Santy; Vina Aditya Astuti; Dewi Andang Prastika (Journal of Applied Health Management and Technology, 2025)
Anemia in adolescent girls is a global public health issue that affects nutritional status and future reproductive outcomes. Adolescents with anemia are at higher risk of delivering stunted offspring, making anemia prevention essential in breaking the intergenerational cycle of malnutrition. This study aimed to analyze factors associated with anemia among adolescent girls as an effort to prevent stunting. This cross-sectional study was conducted at SMPTQ Pangeran Diponegoro, Semarang, from August to December 2023. A total of 92 female students aged 10–15 years who met the inclusion criteria were selected using total sampling. Data were collected using questionnaires and physical measurements, including hemoglobin levels, BMI, MUAC, and dietary intake. Data were analyzed using chi-square tests (α = 0.05). The prevalence of anemia was 25%. Menstrual duration was significantly related to anemia (p = 0.041; RR = 2.188). Other factors (BMI, MUAC, breakfast habits) were not significant. Menstrual duration was significantly associated with anemia among adolescent girls. School-based anemia screening and nutrition education are recommended to prevent anemia and future stunting.